Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah, Dana Alokasi Umum, dan Dana Alokasi Khusus terhadap Pengalokasian Belanja Modal: Studi Pada Pemerintahan Kabupaten/Kota di Jawa Timur Periode 2018-2020 - Erina Setiana Putri; Nur Ika Mauliyah (Jurnal Akuntansi Terapan dan Bisnis, 2022)
Capital expenditure is one of the regional expenditures that needs to be taken into account in the development of sustainable infrastructure and facilities. The existence of regional revenues consisting of PAD, DAU, and DAK which are used to improve public services through public facilities will be able to increase capital expenditure so that economic growth will also increase. This study aims to determine the effect of economic growth, local revenue, general allocation funds, and special allocation funds on the allocation of capital expenditures. This research uses a quantitative research approach with descriptive research types. The population in this study are 38 districts/cities in East Java Province. The sampling method in this study used saturated sampling method, the number of samples used in this study was 114 (38 x 3). Data collection techniques and instruments in this research are literature studies and documentary studies. The data analysis used was descriptive statistics, classical assumption test, simple and multiple linear regression hypothesis testing with the help of the SPSS program. The results of this study can be concluded that: economic growth has a negative and significant effect on the allocation of the Capital Expenditure budget while PAD, DAU, and DAK partially have a positive and significant effect on the allocation of the Capital Expenditure budget. The variables of economic growth, PAD, DAU, and DAK simultaneously have a significant effect on capital expenditure.